Primary microbiological screening of polyphenol extracts isolated from plant materials - Osolodchenko, Tetyana; Andreeva, Irina; Komisarenko, Mykola; Zavada, Nadiya; Ryabova, Irina (Annals of Mechnikov’s Institute, 2021)
Introduction. In the conditions of constantly progressing resistance of microorganisms to antibacterial chemotherapeutics the specialists turn to the natural treatment approaches, especially towards plants that possess antibacterial activity. The aim of the work is to study the antimicrobial properties of polyphenolic compounds of plant origin by primary microbiological screening. Materials & methods. Primary microbiological screening of the 74 polyphenol extracts isolated from plant raw materials was performed. The isolation of phenolic compounds was carried out by extraction with ethanol of various concentrations, water or methylene chloride. Determination of the content of polyphenols in the extracts was performed by spectrophotometric method. For the primary screening standard test cultures of gram-positive and gram-negative bacteria were used that belonged to different taxonomic groups: Staphylococcus aureus ATCC 25923, Esсherichia coli ATCC 25922, Pseudomonas aeruginosa ATCC 27853, Bacillus subtilis ATCC6633, Proteus vulgaris ATCC 4636. Antifungal activity of the compounds was studied for the reference strain of Candida albicans ATCC 885-653. Determination of antimicrobial and anticandidal activity of the new compounds was carried out with the help of the diffusion method of "wells" with the measurement of the diameters of the zones of growth retardation of microorganisms. Results & discussion. The primary microbiological screening of the of the 74 polyphenolic extracts isolated from plant raw materials has shown significant and moderate antimicrobial activity of the polyphenolic compounds against reference strains of gram-positive (S.аureus АТСС 25923, B. subtilis ATCC 6633) and gram-negative (P. vulgaris ATCC 4636, E. coli АТСС 25922, P. aeruginosa ATCC 27853) microorganisms and antifungal activity against Candida spp. fungi (C. аlbicans ATCC 885-653). 66.7% of polyphenol extracts from apricot pericarp were highly and moderately active against S. aureus ATCC 25923, 91.7% - against B. subtilis ATCC 6633, 83.3% - against E. coli ATCC 25922 and 66.7% - against P. vulgaris ATCC 4636. Half of the studied extracts of pericarp of apricot ordinary also showed high or moderate activity against P. aeruginosa ATCC 27853 and C. albicans ATCC 885-653. Among the 36 extracts of polyphenols from common apricot, the most active were polyphenolic compounds extracted from the pericarp of common apricot with 70.0% and 96.0% ethanol in combination with hydrochloric acid. They showed high antimicrobial activity against all studied reference strains of microorganisms (diameters of growth retardation zones in the range from (25.0 ± 0.8) mm to (31.7 ± 1.2) mm). 66.7% of apricot wood extracts were highly or moderately active against S.aureus ATCC 25923, 75.0% - against B. subtilis ATCC 6633 and E. coli ATCC 25922, over 50.0% - against P. vulgaris ATCC 4636, P. aeruginosa ATCC 27853 and C. albicans ATCC 885-653. All 100.0% of dried apricot fruit extracts showed high or moderate antimicrobial activity against all studied reference strains of microorganisms. High sensitivity to S. aureus ATCC 25923, E. coli ATCC 25922 and P. aeruginosa ATCC 27853 was found for 20.0%, to B. subtilis ATCC 6633 - to 40.0%, to P. vulgaris ATCC 4636 - for 10.0% of the studied samples of extracts of raspberry polyphenols. Among the 10 samples of extracts of polyphenolic compounds extracted from raspberries the most active were polyphenols extracted from the wood and leaves of raspberries with water with the addition of emulsifier tween-80. They showed high antimicrobial activity against almost all studied reference strains of microorganisms (diameters of growth retardation zones in the range from (24.3 ± 0.5) mm to (34.3 ± 0.5) mm). According to the results of primary microbiological screening of 16 alcoholic extracts of cultivated grapes for further research whole extracts from vines and leaves, extracted with ethanol 96.0% were selected. The most sensitive to extracts of polyphenols isolated from grapes were test strains of gram-positive microorganisms (S. aureus ATCC 25923, B. subtilis ATCC 6633) (diameters of growth retardation zones ranging from (35.3 ± 0.5) mm to (37, 7 ± 0.5) mm). The effect of the studied extracts on the test strain of E. coli ATCC 25922 was almost similar. Among the studied 12 plant extracts, which contain flavonoids as the leading group of biologically active compounds, only alcohol extract from eucalyptus twigs showed high antimicrobial activity against all studied reference strains of microorganisms (diameters of growth retardation zones in the range from (25.3 ± 0.5) mm to (29.7 ± 0.5) mm). High sensitivity of gram-positive microorganisms has been established to alcohol extracts of polyphenols from cherry wood, blackcurrant leaves and wood and eucalyptus leaves (diameters of growth retardation zones in the range from (25.1 ± 0.5) mm to 29.7 ± 0.5 ) mm). High activity of alcoholic extract of willow against P. aeruginosa ATCC 27853 (diameter of the growth retardation zone (34.3 ± 0.9) mm) and C. albicans ATCC 885-653 (diameter of the growth retardation zone) (29.7 ± 0.5 ) mm) draws attention to itself. Conclusion 1. According to the results of the primary microbiological screening of the 74 extracts of polyphenols, which were isolated from plant raw materials, the most active were the extracts from the apricot pericarp, extracted for the additional combination of 70.0% and 96.0% of in combination with hydrochloric acid; extracts from wood and raspberry leaves, extracted with additional water from additional emulsifier twin-80; whole extracts of vine and grape leaves, extracted with ethanol 96.0%; alcoholic extracts from the leaf of eucaliptus, alcohol extract of twigs with willow buds, wood and leaves of black currant, wood and leaves of cherry.2.According to the results of the primary microbiological screening for further more detailed study of the spectrum and levels of antimicrobial activity, the most promising extracts in order to develop new antimicrobial agents based on them were selected. Keywords: extracts of plant polyphenols, microorganisms, antimicrobial activity DOI: 10.5281/zenodo.5499705